(untitled) (Global Journals of Research in Engineering, 2012)
In view of the ever-increasing demand for energy and ever increasing operating pressure of line pipe it is very essential to develop high strength steel and production technology for manufacturing the line pipes of high strength of level to X-120M Recent experiments show that the grade X- 80M with respect to grade X-70M could give investment cost saving of pipe line construction project if we use X-120M steel line pipes the cost saving is much higher Therefore economic transport of gas from remote sources is an important consideration in today s global economic environment To solve these challenges a high strength grades large diameter line pipe of X-120M strength level through J-C-O-E technique has to be developed The J-C-O-E longitudinal double submerged arc welding LDSAW of X- 120M line pipe has major challenge to establish the toughness for heat affected zone HAZ at theX-120M strength level as the SAW welding is high heat input welding process So the maintaining the strength and toughness at the strength level of X-120M of heat affected zone HAZ is very critical as the cooling rate is very high